Case series: Cariprazine in early-onset schizophrenia - Ivanova, Elena; Maslinkova, Desislava; Polnareva, Nadia; Milanova, Vihra (Frontiers in Psychiatry, 2023)
Introduction Negative symptoms are part of the clinical manifestations of schizophrenia and their presence is associated with a poorer prognosis, significantly limited vocational opportunities, impaired quality of life and social functioning. In the clinical practice, treatment of negative symptoms in patients with schizophrenia, is a challenge. Cariprazine is a novel partial agonist of D3 and D2 receptors, and shows a high affinity for D3, with good tolerability, good response to schizophrenic symptoms and limited side effects. We present two cases of young patients with predominantly negative symptoms during treatment with an atypical antipsychotic, administered in a stable dose and therapeutic range, and for at least 4 weeks prior to the Cariprazine switch. Methods Two patients (men aged 21 and 22) with schizophrenia, exhibiting predominantly negative symptoms, are presented. Their diagnosis was based on, DSM-5 criteria (295.10). Patients were treated with Cariprazine at a daily dose of 4.5 mg. They were followed for a period of 18 months and assessed with Positive and Negative Syndrome Scale (PANSS), Global Assessment of Functioning (GAF) and Clinical Global Impression-Severity (CGI-S), at the fourth week of initiation of treatment with Cariprazine, at 6 months, at 12 months and at 18 months. Their mean initial value was 75.5 on PANSS, 4.0 on CGI-S, and 52.5 on GAF. Both patients were treated with stable doses of atypical antipsychotic–Risperidone at a daily dose of 4,5 mg. Cross-titration to Cariprazine was initiated, from 1.5 mg daily dose up to 4,5 mg daily dose, during a period of 2 weeks. Results After 18 months of treatment with Cariprazine at a daily dose of 4.5 mg, the following results were reported: mean value was 57.5 on PANSS, 3.0 on CGI-S, and 74.5 on GAF. The overall PANSS mean score decreased by 23.8%, the CGI-S mean score improved by 25% and the mean GAF score increased by 29.5%. The positive PANSS subscale score decreased minimally, from 20 to 16, while for the negative subscale the improvement was 29.8%. Cariprazine was well tolerated by patients and no side effects were observed from it during therapy. Discussion After 18 months Cariprazine succeeded in improving negative symptoms, global functioning, and global clinical impression. In young schizophrenic patients with a predominance of negative symptoms, the cariprazine may be a successful alternative.